Evaluation of renoprotective effect of Chinese chive extracts on adenine-induced chronic renal failure - Qiang-Ming Li; Jian-Ping Luo; Li-Hua Pan; Xue-Qiang Zha (Food Science and Human Wellness)
The renoprotective effects of Chinese chive water and ethanol extracts (CCWE and CCEE) on adenine-induced chronic renal failure (CRF) mice were evaluated in this study. Results showed that the renal pathological damages and the enhancement of serum creatinine and blood urea nitrogen of CRF mice could be significantly alleviated by the treatment of CCWE, but not CCEE. When the concentration of CCWE reached 200 mg/kg/day, the area of renal pathological damage was decreased to the 48.1% of model group, and the levels of serum creatinine and blood urea nitrogen were decreased to the 87.7% and 83.9% of model group, respectively. Meanwhile, it could be found that renal oxidative stress and inflammation of CRF mice were remarkably inhibited by CCWE. These results indicated CCWE could improve the kidney function of CRF mice via enhancing antioxidant ability and inhibiting inflammation, and was the main renoprotective fraction of Chinese chive. Keywords: Chinese chive, Renoprotection, Chronic renal failure